Tanggung Jawab Pemerintah Daerah Terhadap Pekerja Anak - Doni Natar; Saartje Sarah Alfons; Ronny Soplantila (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Child labor is an important and complex issue in many countries, including Indonesia. The responsibility of local government in protecting the rights and welfare of child workers is a major concern. This study aims to analyze the considerations that must be made by local governments in addressing the problem of child labour. Local government can play a significant role in protecting the rights and welfare of child workers. These steps need to be supported by strong political commitment, adequate resource allocation, and synergy between all relevant stakeholders. The results of the research show that local governments have an important responsibility in protecting child labour. The consideration that must be made by the local government is to ensure that there is effective supervision in protecting child workers. This involves close monitoring of industries that have the potential to employ children, as well as strict law enforcement against violations of child labor rights and local governments must also adopt clear policies and regulations to protect child labour. This involves drafting regulations that limit access and prohibit child labor in hazardous industries, as well as providing protection and access to education and health.